The Effect of Nursing Students' Climate Change Awareness and Eco-Anxiety Levels on Gender Perception: A Cross-Sectional Study - Küçükkaya, Burcu; Temiz, Mehtap (KTO Karatay University, 2025)
Objective: This study aims to examine the effect of nursing students' awareness of climate change and their levels of eco-anxiety on their perceptions of gender roles. Materials and Methods: This cross-sectional study was conducted between 23 September 2024 and 10 October 2024, involving 331 students from the Nursing Department of a state university Faculty of Health Sciences. The study utilized the Personal Information Form, the University Students' Climate Change Awareness Scale (USCCAS), the Eco-anxiety Scale (EAS), and the Gender Perception Scale (GPS). Results: The students’ mean of USCCAS, EAS and GPS scores was 72.81±14.91, 13.49±7.14, and 93.09±18.11, respectively. A statistically significant weak positive relationship was found between USCCAS and GPS(p<.001), while no significant relationship was identified between USCCAS and EAS. A statistically significant weak negative relationship was found between GPS and EAS(p<.001). Conclusion: As students' awareness of climate change increases, their perception of gender roles improves, and as their gender role perception increases, their eco-anxiety decreases. Based on these results, it is recommended that women's health and disease nurses provide training on climate change, eco-anxiety, and gender perception for university students.

Amaç: Bu çalışmada, hemşirelik öğrencilerinin iklim değişikliği farkındalığı ve eko anksiyete düzeylerinin toplumsal cinsiyet algısı üzerine etkisini incelemek amaçlandı. Gereç ve Yöntemler: Kesitsel özellikte yürütülen bu çalışma, 23.09.2024-10.10.2024 tarihlerinde bir devlet üniversitesinin Sağlık Bilimleri Fakültesi Hemşirelik Bölümü’nde okuyan 330 öğrenci üzerinde uygulandı. Araştırmada Kişisel Bilgi Formu, Üniversite Öğrencilerinin İklim Değişikliği Farkındalık Ölçeği (ÜÖİDFÖ), Eko-Anksiyete Ölçeği (EAÖ) ve Toplumsal Cinsiyet Algısı Ölçeği (TCAÖ) kullanıldı. Bulgular: Üniversite öğrencilerinin ÜÖİDFÖ, EAÖ ve TCAÖ toplam puan ortalaması sırasıyla 72,81±14,91, 13,49±7,14 ve 93,09±18,11 olarak hesaplandı. Üniversite öğrencilerinin ÜÖİDFÖ ile TCAÖ arasında istatistiksel olarak pozitif yönlü zayıf düzeyde anlamlı ilişki bulunurken(p<.001), EAÖ arasında istatistiksel olarak anlamlı ilişki belirlenmemiştir(p>.05). TCAÖ ile EAÖ arasında istatistiksel olarak negatif yönlü zayıf düzeyde anlamlı ilişki bulundu(p<.001). Sonuç: Üniversite öğrencilerinin iklim değişikliği farkındalık düzeyi arttıkça, toplumsal cinsiyet algısı artmakta ve toplumsal cinsiyet algısı arttıkça, eko-anksiyete azalmaktadır. Bu sonuçlar doğrultusunda, kadın sağlığı ve hastalıkları hemşirelerinin üniversite öğrencilerine yönelik iklim değişikliği, eko-anksiyete ve toplumsal cinsiyete yönelik eğitimler vermesi önerilmektedir.
Hemşirelik Öğrencilerinin İklim Değişikliği Farkındalığı ve Eko Anksiyete Düzeylerinin Toplumsal Cinsiyet Algısı Üzerine Etkisi: Kesitsel Çalışma
Keywords: Obstetrics and Gynocology Nursing; Doğum ve Kadın Hastalıkları Hemşireliği